2012
DOI: 10.3892/ijo.2012.1744
|View full text |Cite
|
Sign up to set email alerts
|

Molecular features of triple negative breast cancer cells by genome-wide gene expression profiling analysis

Abstract: Abstract. Triple negative breast cancer (TNBC) has a poor outcome due to the lack of beneficial therapeutic targets. To clarify the molecular mechanisms involved in the carcinogenesis of TNBC and to identify target molecules for novel anticancer drugs, we analyzed the gene expression profiles of 30 TNBCs as well as 13 normal epithelial ductal cells that were purified by laser-microbeam microdissection. We identified 301 and 321 transcripts that were significantly upregulated and downregulated in TNBC, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
589
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 309 publications
(600 citation statements)
references
References 46 publications
(59 reference statements)
9
589
0
2
Order By: Relevance
“…Taken together, we find the role of these non-epithelial cells present in TNBCs (even though a minority population) an important aspect of the analysis. Further, to independently validate our findings, we compared our differentially expressed genes (Supplementary Table 1) to a recently published set of differentially expressed genes derived from 30 microdissected TNBCs and 13 normal ductal epithelium using microarrays [41]. We validated by determining the number of overlapping genes between the two datasets where the direction of the fold-change was the same and the p-value<0.05.…”
Section: Discussionmentioning
confidence: 88%
“…Taken together, we find the role of these non-epithelial cells present in TNBCs (even though a minority population) an important aspect of the analysis. Further, to independently validate our findings, we compared our differentially expressed genes (Supplementary Table 1) to a recently published set of differentially expressed genes derived from 30 microdissected TNBCs and 13 normal ductal epithelium using microarrays [41]. We validated by determining the number of overlapping genes between the two datasets where the direction of the fold-change was the same and the p-value<0.05.…”
Section: Discussionmentioning
confidence: 88%
“…Most of the current methods for TNBC detection are based on analysis of gene expression profiles [128, 129] or sensing of antibody array platforms [130], which are generally tedious and time consuming processes that require well-trained technical personnel in well-equipped laboratories. It is also clear that TNBCs are a diverse and heterogeneous group of tumors; a single molecule may not distinguish them.…”
Section: Resultsmentioning
confidence: 99%
“…PBK also interacts with p53 to regulate expression of cell cycle genes [8]. Multiple studies have found that PBK overexpresses in breast, prostate, colon, bladder, and lung cancers and is a prognostic biomarker for poor outcomes [2-5]. Previous studies have shown that expression of PBK is regulated by Myc and E2F1 transcriptional factors [34].…”
Section: Discussionmentioning
confidence: 99%
“…PBK is overexpressed in multiple types of cancer, including breast, prostate, colon, bladder, and lung cancer, but is undetectable in normal tissues except germ cells in the testis and several fetal tissues [2-5]. PBK mediates UVB-induced JNK activation and facilitates H-Ras-induced cell transformation [6].…”
Section: Introductionmentioning
confidence: 99%